Refugees to the Rescue? Motivating Pro-Refugee Public Engagement During the COVID-19 Pandemic. Issue 3 (13th April 2022) - Adida, Claire L.; Lo, Adeline; Prather, Lauren; Williamson, Scott
Abstract: Migrants are often scapegoated during public health crises. Can such crises create opportunities for migrant inclusion instead? As the COVID-19 pandemic unfolds, many refugee organizations have stepped up their outreach with stories of refugees helping out in the crisis. We have partnered with the country's leading refugee advocate organizations to test whether solidarity narratives increase public engagement with refugee advocates. We employ a Facebook experimental design to evaluate the effectiveness of refugee narratives. We test whether (1) migrant narratives framed in the context of COVID-19, (2) COVID-19 migrant narratives targeted to more or less local communities, and (3) COVID-19 migrant narratives labeled as refugee vs. immigrant efforts enhance public engagement with refugee organizations. Our results indicate that migrant narratives framed in the context of COVID-19 do not motivate greater engagement than those that make no mention of the pandemic. Our results provide suggestive evidence that locally targeted efforts motivate greater engagement. Finally, we find no difference between the "refugee" and "immigrant" label, but we show that both labels can motivate greater engagement than ads that include neither. Importantly, this is true even in the context of COVID-19, an uncertain environment where worries of backlash might be warranted. These results suggest promising strategies for migrant policy organizations to promote engagement during and possibly after the pandemic.